A QUEST FOR MONETARY AND FINANCIAL REFORMS IN INDONESIA - Mudrajad Kuncoro (Journal of Indonesian Economy and Business (JIEB), 1994)
Indonesia in the 1980s provides an unusual and unique example of substantial, albeit gradual, deregulation and rapid development of a domestic financial system. The monetary and financial reforms were part of larger packages of economic reforms designed to stabilize and restructure the economy.First of all, this paper reviews briefly the framework of financial repression theory. Secondly, It examines the major monetary and financial reforms undertaken by Indonesia during the 1980s. The next section discusses the Indonesian experience in the period financial repression and liberalization. The question may arise: how far the reforms have changed the financial sector. To test whether financial reforms influence the real economy, the last section will investigate the effect of financial liberalization on Inflation and economic growth.The empirical investigations find that the positive relationship between Inflation and economic growth shows an evidence of short-run Phillips curve in Indonesia. The short-run Phillips curve is typical of a modified Phillips curve with the credit-availability effect added. The study also Indicates that the financial deregulation, triggering a period of positive real interest rates, has statistically affect the economic growth profoundly. Yet, the real deposit rates of interest does not Influence the growth of real GDP significantly.